Epidemiology and outcome of Klebsiellapneumoniae carbapenemase-producing Klebsiella pneumoniae (KPC-KP) infections in cardiac surgery patients: a brief narrative review. (17th November 2019) - Del Puente, Filippo; Giacobbe, Daniele R.; Salsano, Antonio; Maraolo, Alberto E.; Ong, David S.Y.; Yusuf, Erlangga; Tutino, Stefania; Marchese, Anna; Santini, Francesco; Viscoli, Claudio
Abstract : Klebsiella pneumoniae carbapenemase-producing Klebsiella pneumoniae (KPC-KP) is a difficult-to-treat pathogen due to its multidrug-resistant phenotype. Cardiac surgery patients are at increased risk of developing KPC-KP infections compared to other populations, with previous KPC-KP colonization being a critical factor in influencing the risk of subsequent infection. Two different pieces of information are essential to comprehensively assess the local characteristics of KPC-KP colonization in cardiac surgery patients: ( i ) the local prevalence of colonization; ( ii ) the timing of colonization. Treatment of KPC-KP infections in cardiac surgery patients is a complex task, but more effective treatment options have recently become available. Nonetheless, implementation and full adherence to infection-control measures remain of pivotal importance for reducing the burden of KPC-KP infections in this peculiar population. The aim of this narrative review is to summarize the available literature on the epidemiology and outcome of KPC-KP infections in cardiac surgery patients.